Vismia glaziovii Ruhl. (Guttiferae) seed size and its relationship with the germination speed and seedling size - Arteaga, Luis L. (2007)
In the present work I analyzed the variability of the seeds size of Vismia glaziovii Ruhl. and its Vismia glaziovii Ruhl. and its Vismia glaziovii possible effect on germination speed and its seedling size. The results show that the size of the seeds does not vary signifi cantly between trees from which they came; but the variation as large as seed between the fruits of each tree is signifi cant. Also, the size of the seed does not infl uence the speed of germination nor the seedling size. We suggested that variability in size is not suffi cient as indicator of differences in the amount of stored resource. This study will allow contributing to the knowledge of some aspects of the dynamics of seeds and the regeneration of this species.